LEARNING MANAGEMENT SYSTEM (LMS) CLAROLINE PADA PERANGKAT MOBILE ANDROID - Kurnia Muludi; Ossy Dwi Endah Wulandari; Dedi Kurniawan (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
E-Learning nowadays is still accessible via the web browser. E-Learning has a server named Learning Management System (LMS). LMS consists of a paid, unpaid and a tailor (version specially ordered). For this research, LMS is used which is not paid. There are lots of LMS are not paid, one of these is Claroline. The development of E-Learning is followed by the development of mobile devices such as Android devices. Android usage has increased each year but applications for E-Learning are still underdeveloped. Based on this background, then it is needed to develop an E-Learning application on Android mobile devices, because Android devices can support the development of client applications of E-Learning. The purpose of developing this application is to enable users who use Android devices to download the file from existing lecture materials wherever, whenever they want through their Android devices.In this research, the application is developed using Eclipse as an IDE using Java programming language for Android, XML, and of course the Claroline as the LMS server. This application is the complement of Claroline which is normally access through a web browser.The results of this research show that the client application is able to download files that exist on the lecture materials from Claroline server.Â Keywords : E-Learning, Android, Learning Management System, Claroline, Mobile Application, E-LearningApplication